A potência narrativa da violência e do sobrenatural: suas configurações estéticas e temáticas em “Makiné”, de Guimarães Rosa, e “A torre do elefante”, de Robert E. Howard - Almeida, Igor Gonçalves (2023)
Sword and Sorcery is a literary subgenre whose name immediately suggests the relationship between violence and the supernatural, present in literature since its dawn. It is found in the stories of author Robert E. Howard, full of violent and supernatural adventures, the reason for such a title to be coined. In Brazil, Guimarães Rosa, wove a literature in the thirties of the 20th century that, in its themes and configurations of the narration, are very similar to that of its American contemporary. This opens up the possibility of building a bridge to analyze how the representations of violence and the supernatural are configured, as well as the relationship between both, understood as basic aesthetic and thematic devices, within the two stories in question. It is based on the hypothesis that the way in which violence and the supernatural are represented is one of the determining aesthetic and structural characteristics of the stories in question, establishing the pace at which it intensifies and how it is experienced by the reader, allowing them to characterize and contrast the duality among other topics addressed. It is also possible to apprehend that the relationship between violence and the supernatural, within the narratives, works as an artifice that tensions the narrative to its climax through the way in which they are inserted in the structure of the story itself. The theoretical assumptions, basic to the research in question, are: Poe and his basic theory about the configurations of the short story genre; Cortázar and his expansions in short story theory regarding tension and intensity; Piglia and his reflection on the double character of the short story; Bruno Matangrano and Enéias Tavares with their analysis of the fantastic genre; H.P Lovecraft and his reading of the supernatural in literature; Hanna Arendt and her reflections on violence; René Girard and his views on the connection between violence and mimetic desire; and Jaime Ginzburg, with his analysis of the links between literature, violence, and authoritarianism. The research will be carried out using a qualitative and descriptive methodology, following an analytical, hypothetical-deductive method. In the end, it is understood that the supernatural, an unusual form of violence, establishes tension through the level of absurdity experienced, built by the encounters between the stories of the stories and the gaps left in the act of narrating, an act of memory resistance